Hazard-Specific Competency in Earthquake and Building Collapse for Local Administrative Organizations’ Disaster Risk Reduction - Wichaipa, Kanrawee (Local Administration Journal, 2021)
Disaster management is an important mission of local administrative organizations to prepare for disaster prevention and develop a capacity to respond and assist victims and reduce the impact of disasters, especially natural disasters such as earthquakes and building collapses. Local administrative organizations are the agencies that are closest to the people, so it is an important agency. This research had two objectives: 1) to study the disaster-specific performance of disaster prevention and mitigation workers in disaster risk reduction operations for earthquake and building collapse; and 2) to develop indicators of competence of employees working in disaster prevention and mitigation in earthquake and building collapse disaster risk reduction operations for local administrative organizations in Thailand. The author employed a qualitative research design with document analysis, in-depth interviews, group discussion, and content analysis. The research found that local administrative organizations should apply competency systems to manage and develop their human resources for disaster risk reduction. The disaster-specific competencies of earthquake-prone areas consisted of five levels of competence: 1) advising on houses and other buildings; 2) mapping and evacuation planning for people in the area; 3) search and rescue operations in earthquake situations; 4) situation assessment and coordination of information on earthquakes and building collapses; and 5) public communication in areas at risk of earthquakes and building collapses.